Costume and Body Language of Ethnic Dance Drama under Semiotics: An Analytical Study - Pan, Chong; Alizadeh, Farideh (Journal of Ecohumanism, 2024)
Dance drama is a dramatic form with dance as its main means of expression, which has been developed in China for less than a century. In recent years, the development of Chinese dance drama, especially ethnic dance drama, has shown an obvious upward trend. Several excellent dance drama works have appeared, forming some distinctive dance drama styles, among which The Journey of a Legendary Landscape Painting, The Peacock, and The Railway to Tibet are quite representative. This study will investigate the above three dance dramas based on semiotics. An analysis of costume and body language is carried out in this study based on the semiotics, from the morphological characteristics of dance and costume. In addition, the author makes a comprehensive exploration of the integration of the external form, fabric, structure and pattern of costume and body language, tries to reveal the way of interaction between costume symbols and body symbols in dance drama, and summarises the artistic connotation of the integration of dance costumes and body language. Then, it provides ideas for the role creation and education of dance drama.